The Impact of Website Management on MSMEs in Pabelan Village, Semarang Regency - Erico Indra Martha; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the influence of website management on the development of Micro, Small, and Medium Enterprises (MSMEs) in Pabelan Village, Semarang Regency. In today's digital era, websites have become an essential part of marketing strategies and business development. This study employed a qualitative approach through interviews and observations of 15 MSME owners who have implemented websites as marketing tools. The results show that proper website management positively impacts market reach, sales, and ease of information access for consumers. MSME owners who actively update content, improve appearance, and respond to customer interactions through their websites experienced an average revenue increase of 35%. These findings emphasize the importance of digital literacy and technical assistance for MSME actors in optimizing their website management as a means of business development in the digital economy era.